The impact of higher education on innovation: A comparison of Slovenia and Switzerland - Anja Car; Peter Stanovnik (Mednarodno Inovativno Poslovanje)
Knowledge transfer between universities and industry and their impact on innovation is nowadays a key research topic in both economic studies and science and technology policy in many developed and developing countries. In this context, we investigated the impact of higher education on the current state of innovation in Slovenia in comparison with Switzerland. The Switzerland represents an incubator of future strong innovators and Slovenia a group of modest innovators. Switzerland has the world's highest innovation index, and this success is based on human resources that have the right skills to contribute to innovative solutions to improve living standards, the environment and economic development. Considering that Slovenia's strongest attributes are also its human resources, Slovenia should be a country that is recognizable for its innovative and highly technologically oriented companies in selected niches on the world market. The work is based on the comparison of univeristies and their impact on innovation in the context of the analysis of the publication of scientific articles, the number of patents and the number of newly founded companies.